Caiaphas’s Prophecy: Christian Cledonomancy in John 11:45–53 - Crosby, Daniel J. (Novum Testamentum, 2026)
Commentators on John 11:45-53 have understood John’s account of Caiaphas’s unintended prophecy within a strictly Jewish context. Either it is claimed that prophetic power was understood as fundamentally tied to the Jewish priesthood, or it is compared to similar instances of prophecy discussed in rabbinic tradition. In this article, the author shows the inadequacy of these attempts at providing a meaningful context for Caiaphas’s prophecy and argues instead that Greek κληδόνες and Roman omina offer the most strikingly comparable material. The author concludes by suggesting that the influence of Greek culture occasioned a development to the Jewish and Christian concept of prophecy.